REFLECTIVE THINKING STRATEGIES FOR DEVELOPING EFL LITERARY READING SKILLS AND METACOGNITIVE READING AWARENESS - Eman Mahmoud Alian (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
The present study is aimed at examining the effect of reflective thinking strategies on developing literary reading skills and metacognitive reading awareness of the EFL student teachers. The study adopted the quasi-experimental design. One experimental group of 40 major English students at the third-year Faculty of Education, Zagazig University in Egypt, participated in the study. The treatment conducted in fourteen sessions through teaching King Lear drama by Shakespeare. The utilized instruments included a literary reading test that was developed and used as a pre-post test and a metacognitive reading awareness scale, which was also designed by the researcher and approved by the jury members. Parametric statistical calculations have used for data analysis through the SPSS program. Results revealed that reflective thinking had a positive effect on developing literacy reading skills and metacognitive reading awareness of the EFL student teachers.